2019
DOI: 10.1097/bpo.0000000000001464
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Results of Primary Versus Repeat Hamstring Surgical Lengthening in Cerebral Palsy

Abstract: Background: Hamstring surgical lengthening (HSL) has been frequently performed for the correction of knee flexion deformity in cerebral palsy (CP), although recurrence is described in long-term follow-up. Repeat hamstring surgical lengthening (RHSL) can be an option for recurrent knee flexion deformity; however, the results of this approach are still controversial. The purpose of this study was to compare the results of primary HSL and RHSL in CP. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…In terms of the first issue, the overall efficacy of hamstring surgery, this study of 49 original subjects, showed improvement in passive and dynamic measures at the sagittal plane knee at 1 year post-op, and most importantly, improvement in dynamic knee extension in stance, which was maintained in 60%–70% of patients over a long-term follow-up period (7–15 years), although there was return to baseline of many of the passive measures. The findings are consistent with the study published by Õunpuu et al 18 and Morais Filho et al 20 who reported slight decrease in dynamic knee extension at the long-term follow-up compared to values measured at 1 year post-op, but they felt this could be due to natural progression of gait in children with CP which has been shown to decline over time.…”
Section: Discussionsupporting
confidence: 92%
“…In terms of the first issue, the overall efficacy of hamstring surgery, this study of 49 original subjects, showed improvement in passive and dynamic measures at the sagittal plane knee at 1 year post-op, and most importantly, improvement in dynamic knee extension in stance, which was maintained in 60%–70% of patients over a long-term follow-up period (7–15 years), although there was return to baseline of many of the passive measures. The findings are consistent with the study published by Õunpuu et al 18 and Morais Filho et al 20 who reported slight decrease in dynamic knee extension at the long-term follow-up compared to values measured at 1 year post-op, but they felt this could be due to natural progression of gait in children with CP which has been shown to decline over time.…”
Section: Discussionsupporting
confidence: 92%
“…Problems reported in the literature after HSL include incomplete correction, recurrent crouch, over-correction and recurvatum, increased APT, and less favorable results following revision or repeat HSL. 27 31 Excessive APT has long been identified as a potential problem following HSL, 27 , 30 , 31 with recent authors indicating that APT seems to be an issue in children functioning at GMFCS level III, but not in those functioning at GMFCS levels I–II 31 and appears to be a greater risk following medial and lateral HSL, 27 after revision HSL, 28 and possibly in females. 32 Genu recurvatum may be more common with combined medial and lateral HSL, but can occur after isolated medial lengthening 33 and may be related to plantar flexion–knee extension coupling, due to either residual calf tightness or spasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Such conclusions are supported by previously published literature. 28 , 29 Many panel members noted that repeat HSL (following previous HSL) often is not helpful, thus leading to the increased use of other soft tissue and bony procedures more recently, including anterior distal femoral hemiepiphysiodesis, distal femoral extension osteotomy, patella tendon shortening or advancement, or a combination thereof, for those with recurrent crouch. Alternatives to repeat HSL include guided growth in the skeletally immature patient, distal femoral extension osteotomy (DFEO) with patellar tendon shortening or advancement, and combinations of these procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In cases with dystonia, intrathecal baclofen application was shown to be beneficial [ 52 ]. Depending on the underlying problem, surgical procedures normally consist of derotational osteotomies [ 53 , 54 ], open reduction of hip dislocations with or without concomitant bony procedures [ 55 , 56 , 57 ], tenotomies [ 58 , 59 , 60 , 61 , 62 ] or guided growth with temporal (hemi) epiphysiodesis [ 63 , 64 , 65 , 66 ]. Care has to be taken with tenotomies for gaining more range of motion (ROM) of the affected joints which is generally accompanied by a further weakening of the muscle in our clinical experience.…”
Section: Preterm-related Orthopedic Disordersmentioning
confidence: 99%